Conners 3–Self-Report Scale: An empirical support to the dimensionality of the content scales. - Izzo, Viola Angela; Donati, Maria Anna; Primi, Caterina (Clinical Child Psychology & Psychiatry, 2018)
The Conners’ Rating Scales are one of the most used instruments for attention deficit/hyperactivity disorder (ADHD). Nonetheless, in the latest edition, the Inattention scale was not statistically supported. This study examined the dimensionality of the Italian version of the Conners 3–Self-Report scale testing both a five-factor structure including Inattention and a four-factor model combining Inattention and Learning Problems. Moreover, the generalizability of the detected structure through measurement invariance was verified. The Italian version of the scale was completed by 971 children (53% males, mean age: 12.76 years) randomly split in a calibration sample (n = 464) and a validation sample (n = 507). Confirmatory factor analyses detected a five-factor structure (i.e. Inattention, Hyperactivity/Impulsivity, Learning Problems, Defiance/Aggression, and Family Relations), and measurement invariance was confirmed. Findings provided statistical evidence for the Inattention subscale, supporting the Conners 3–Self-Report Scale as effectively aimed to assess the two dimensions of ADHD and its main comorbid difficulties.